Implementation of electronic communications in accounting of public procurement - Pochynok, Nataliia; Muravskyi, Volodymyr; Farion, Volodymyr (Technology audit and production reserves, 2021)
The object of research is the public procurement system in terms of accounting for the processes of buying (selling) goods (works, services) using electronic communications. A problematic aspect of modern electronic public procurement platforms is the lack of information support for accounting, control and taxation functions. In the context of the development of innovative computer and communication technologies, it becomes possible to integrate various electronic services and electronic communications into the public procurement system in order to automate accounting processes. In the process of studying the prospects for the implementation of a system of public communications with expanded functional capabilities, general scientific empirical, logical and historical methodological methods of cognition of reality were used. The theoretical and methodological aspects of improving the accounting of public procurement in the context of the formation of an innovative electronic platform for business communications were studied on the basis of institutional and innovative methods of scientific research. The paper proposes to place electronic contracts at the heart of the business communications system. A procedure has been developed for business interaction between participants in electronic trading through the mechanism for concluding and executing electronic contracts for the purchase (sale) of goods (works, services). Based on the creation of a system of electronic contracts, it is possible to form a database of credentials. The expediency of using accounting information for the automated implementation of public procurement accounting procedures has been substantiated. The methodology for accounting for the occurrence and repayment of accounts payable and receivable for purchased (sold) goods (works, services), charging and paying taxes and fees, electronic money transactions in various currencies, electronic money and cryptocurrency, the occurrence of credit obligations, calculating the amount of bad debts has been improved. The implementation of a public procurement system with expanded functionality will facilitate the establishment of effective business communications with contractors, the integration of disparate electronic services into a single system. As well as minimizing costs in the process of electronic trading, automating the processing of primary information, optimizing accounting and management processes at the enterprise.